Review on rain induced fruit cracking of sweet cherries (Prunus avium L.), its causes and the possibilities of prevention - Simon, G. (International Journal of Horticultural Science, 2006)
The rain induced fruit cracking is a big, serious and costly problem for cherry growers. Cracked fruits lose their value and they are not marketable because of the poor fruit quality. Cracked fruits have different storage diseases and shorter storage and shelf life. There are many influencing factors of the cherry fruit cracking such as: water uptake; fruit characteristics (fruit size, fruit firmness; anatomy and strength of the fruit skin, stomata in fruit skin, cuticular properties, osmotic concentration, water capacity of the fruit pulp, growth stage of the fruit,); orchard temperature and other environmental conditions; The most effective protection technique is the plastic rain cover over the tree rows. The installation of these equipments is too expensive for the cherry growers. That is the reason why researchers tried to find other less expensive and sufficiently effective ways against the Lim induced fruit cracking. Several calcium formulas: calcium chloride (CaC1,), calcium hydroxide (Ca (OH)2) and calcium nitrate (Ca(NO3)2 ) can be sprayed in appropriate concentration. Spraying with other mineral salts (aluminium and copper salts, borax) and PBRs (Plant Bioregulators) may be also effective to reduce fruit cracking.